A novel insight into green food preservation: Design of equilibrium modified atmosphere packaging (EMAP) based on gas barrier (GB) - gas conductor (GC) blending materials. (30th November 2022) - Li, Siqian; Dong, Hao; Yang, Xingfen; He, Qi
Highlights: Modification of gas permeability was achieved by gas barrier (GB) - gas conductor (GC) blending materials. The prepared EMAP can maintain equilibrium atmosphere with 7.89 ∼ 3.97 % of CO2 and 1.12 ∼ 5.05 % of O2. The EMAP made significant changes in the sensory properties of the preserved peppers during storage. The EMAP can efficiently minimize the chemical variations in the preserved peppers during storage. Packaging with 60 % SPEEK and 40 % PES showed the best effects by maintaining 5.18 % CO2 and 3.16 % O2. Abstract: In this work, the design of equilibrium modified atmosphere packaging (EMAP) was achieved by adjusting gas permeability using gas barrier (GB) - gas conductor (GC) blending material. Sulfonated poly ether ether ketone (SPEEK) was used as promoter for gas permeation, i.e. GC, and introduced into poly ether sulfone (PES) as GB. As the results, the introduction of SPEEK cannot only enhance the gas permeability of the blending material, but also modify the physic and chemical properties. When the blending material used as EMAP for peppers, significant effects were exhibited on inhibiting the variations in sensory, color, texture, and chemical properties of the preserved peppers, especially when the samples preserved in packaging consisted of 60 % SPEEK and 40 % PES, in which suitable atmosphere with 5.18 % v/v CO2 and 3.16 % v/v O2 was maintained. The overall findings revealed the feasibility of GB - GC theory for EMAP design.